Factors Influencing User Adoption of Mobile Payment System: An Integrated Model of Perceived Usefulness, Ease of Use, Financial Literacy, and Trust - Utomo, Fandy Setyo; Suryana, Nanna; Azmi, Mohd Sanusi (Journal of Digital Market and Digital Currency, 2025)
In the digital age, mobile payment systems have revolutionized financial transactions by offering convenience, efficiency, and security. This study aims to explore the factors influencing the adoption of the mobile payment system in Indonesia, focusing on perceived usefulness (PU), perceived ease of use (PEU), financial literacy (FL), and perceived trust (PT). Data was collected from 400 respondents using an online survey and analyzed using SmartPLS 3 software. The results indicate that PU and PEU significantly impact users' intention to use (BI) the mobile payment system, with path coefficients of 0.928 (t-value = 28.570) and 0.955 (t-value = 154.251) respectively. PEU also positively influences PU (β = 0.955, p < 0.001). FL was found to affect PT significantly (β = 0.222, p = 0.006), which in turn influences BI (β = 0.068, p = 0.059), although the direct effect of PT on BI was marginally non-significant. The R^2 values for BI, PT, and PU were 0.977, 0.814, and 0.912 respectively, indicating a high explanatory power of the model. This study extends the Technology Acceptance Model (TAM) by integrating FL and PT, providing a comprehensive understanding of the factors driving mobile payment adoption. The findings offer valuable insights for developers, service providers, and policymakers to enhance user experience, build trust, and improve FL, ultimately promoting higher adoption rates of mobile payment systems. Future research should consider a more diverse population and explore additional factors such as social influence and facilitating conditions to validate and extend these findings further.